2012
DOI: 10.1590/s0100-72032012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação ultrassonográfica de cicatriz uterina pós-cesariana segmentar transversa

Abstract: ResumoOBJETIVO: Avaliar a medida do segmento uterino inferior pela ultrassonografia transvaginal em um grupo de mulheres não grávidas e descrever os achados morfológicos na cicatriz daquelas submetidas à cesárea. MÉTODOS: Estudo retrospectivo para o qual foram avaliadas 155 imagens de ultrassonografias transvaginais obtidas de mulheres no menacme, não grávidas. Os exames foram realizados entre janeiro de 2008 e novembro de 2011. Foram selecionados três grupos: mulheres que nunca ficaram grávidas (Grupo Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Bazzo et al, 21 comparing anterior and posterior isthmus thicknesses, found the latter to be twice that of the former. Overall, these measures decrease with age, but the ratio between anterior and posterior wall thicknesses remains similar across all age groups.…”
Section: Diagnosismentioning
confidence: 95%
“…Bazzo et al, 21 comparing anterior and posterior isthmus thicknesses, found the latter to be twice that of the former. Overall, these measures decrease with age, but the ratio between anterior and posterior wall thicknesses remains similar across all age groups.…”
Section: Diagnosismentioning
confidence: 95%